2017
DOI: 10.1021/acs.iecr.7b01812
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Preparing Poly(vinyl alcohol) Hydrogels: Preparation, Characterization, and Application

Abstract: This work provides a new method to prepare poly(vinyl alcohol) (PVA) hydrogel. Compared with the traditional repeated freeze−thaw method, the physical cross-linking method was adopted to prepare a high-strength hydrogel in one step. The morphology, melting, and crystallization behavior and mechanical properties of the hydrogel were investigated. The hydrogel has a high water content and reswelling rate, as well as a high melting temperature and mechanical strength. It also has a stable crosslinked structure in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 25 publications
0
39
0
Order By: Relevance
“…Hence those nanoparticles were formed within a karaya gum (KG)/poly(vinyl alcohol) (PVA) hydrogel. PVA is a water‐soluble synthetic polymer with the cross‐formula [CH 2 CH(OH)] n , which has been used for hydrogels in wound care, or for textiles or coatings. Since PVA readily forms hydrogen bonds in a symmetrical and regular arrangement, the polymer shows excellent filmability, water solubility, emulsification, and adhesion properties .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence those nanoparticles were formed within a karaya gum (KG)/poly(vinyl alcohol) (PVA) hydrogel. PVA is a water‐soluble synthetic polymer with the cross‐formula [CH 2 CH(OH)] n , which has been used for hydrogels in wound care, or for textiles or coatings. Since PVA readily forms hydrogen bonds in a symmetrical and regular arrangement, the polymer shows excellent filmability, water solubility, emulsification, and adhesion properties .…”
Section: Introductionmentioning
confidence: 99%
“…[7] They are even suitable for application as an implant material that can be fabricated in a personalized way by using a molding procedure [25] or 3D bioprinting. PVA is a water-soluble synthetic polymer with the cross-formula [CH 2 CH(OH)] n , [31] which has been used for hydrogels in wound care, or for textiles or coatings. First steps toward the formulation of a morphogenetically active bioink, applicable for 3D-bioprinting at lower cell concentrations, have been successfully passed.…”
mentioning
confidence: 99%
“…One material to consider is polyvinyl alcohol (PVA), which has been used previously to synthesize biocompatible materials3134 with a high WC 35. The properties of the material can be tailored to specific applications by varying molecular weights of the polymer,36 cross-linking methods,31,32,36–38 solvent composition,39,40 and incorporation with other polymers and nano-composites 41. Studies have shown that PVA-based materials can be designed to be potential substitutes for both artificial cornea42 and human vitreous humour 43.…”
Section: Introductionmentioning
confidence: 99%
“…1,[22][23][24] However the biocompatibility and biodegradability represent some major problems that still need to be tackled, especially in the case of implantable hydrogels. The majority of studies on synthetic polymer hydrogels are based on the use of poly(ethylene glycol)s (PEG), 20,24 poly(vinylpyrrolidone) (PVP), [25][26][27] poly(vinyl alcohol) (PVA), [28][29][30] poly(hydroxyethyl methacrylate) (PHEMA), 19,[31][32][33][34] and more recently poly(2-oxazoline)s (PAOx). 18,[35][36][37] Although, these polymers have certain advantages they all come hand in hand with shortcomings that can limit their applicability as biomaterials.…”
Section: Introductionmentioning
confidence: 99%